Developing employability and professional identity through visual narratives - Bennett, Dawn (Art Education Australia, 2016)
Enhancing employability for higher education arts graduates requires collaborative action on three fronts: specificity in the measurement and reporting of graduate outcomes; advocacy to re-align stakeholder conceptions of graduate work and employability; and learner engagement in career-related thinking and action. This paper reports a career-related engagement in which students and educators created visual narratives with text-based captions in answer to the question, “What is a musician?” Similarities and differences in student-educator thinking highlight the potential for students to generate broad career previews through in-class engagement. Visual methodologies emerge as a powerful strategy for the promotion of career-oriented thinking and reflection.